Pulmonary artery aneurysm as a result of group 2 pulmonary artery hypertension in a patient with significant mitral and aortic valve disease – review and case report - Marzec, Karolina; Jaworska-Wilczyńska, Maria; Grobelny, Konrad; Kołsut, Piotr; Michałowska, Ilona; Stokłosa, Patrycjusz; Hryniewiecki, Tomasz (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2020)
Aneurysms are uncommon, but potentially life-threatening abnormalities of the pulmonary arteries. Aneurysm of the main pulmonary artery (MPA) defined as MPA diameter over 40 mm was reported in 1 : 14 000 autopsies. The most frequent location is the main pulmonary artery (89% of cases), whereas the maximum described diameter is 106–170 mm. Clinical manifestations are usually nonspecific or asymptomatic. Right heart failure symptoms, pulmonary regurgitation, trachea or bronchi compression or pulmonary emboli caused by enlarged MPA are the most commonly described clinical manifestations. Pulmonary artery aneurysm dissection is an uncommon complication but associated with a high mortality rate. Unfortunately, guidelines regulating the optimal time for the surgical intervention still have not been developed. We present the history of 76-year-old patient suffering from an aneurysm of the pulmonary artery (74 × 61 mm), as well as mitral and aortic valve disease, who was successfully operated on in our hospital.